2006
DOI: 10.1021/ac060565z
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-MS Direct Tissue Analysis of Proteins:  Improving Signal Sensitivity Using Organic Treatments

Abstract: Direct tissue analysis using MALDI-MS allows the generation of profiles while maintaining the integrity of the tissue, displaying cellular localizations and avoiding tedious extraction and purification steps. However, lower spectral quality can result from direct tissue analysis due to variations in section thickness, the nature of the tissue, and the limited access to peptides/proteins due to high lipid content. To improve signal sensitivity, we have developed a tissue-washing procedure using organic solvents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
166
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(167 citation statements)
references
References 35 publications
1
166
0
Order By: Relevance
“…It has previously been shown that washing the tissue sections with organic solvents such as chloroform and EtOH before matrix deposition increases the number and intensities of protein signals up to 20 kDa [27][28][29]. To test if the increased high mass sensitivity and charge capacity of the high mass HM1 detector may benefit imaging MS of higher mass proteins, mouse brain tissue sections were washed with chloroform and ethanol, prepared with a matrix solution of 20 mg/mL SA in AcN:0.1% TFA (7:3, vol/vol), and then analyzed using an AutoFlex III MALDI-ToF equipped with an MCP and a HM1 detector.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that washing the tissue sections with organic solvents such as chloroform and EtOH before matrix deposition increases the number and intensities of protein signals up to 20 kDa [27][28][29]. To test if the increased high mass sensitivity and charge capacity of the high mass HM1 detector may benefit imaging MS of higher mass proteins, mouse brain tissue sections were washed with chloroform and ethanol, prepared with a matrix solution of 20 mg/mL SA in AcN:0.1% TFA (7:3, vol/vol), and then analyzed using an AutoFlex III MALDI-ToF equipped with an MCP and a HM1 detector.…”
Section: Resultsmentioning
confidence: 99%
“…Tissues were then submitted to washing procedures prior to matrix application for improved detection of peptides/proteins. Washing was performed by two washing steps using first washing with cold 95% EtOH for 15 s followed by a washing step with chloroform for 1 min according to previously published protocols [11,34].…”
Section: Frozen Tissuesmentioning
confidence: 99%
“…Since then, many improvements in MALDI-MSI performance have been achieved, including improvements related to tissue preparation [10][11][12], data processing and imaging software [13,14], and spatial resolution [15,16]. Biomarker discovery and identification has been a field of intense research over the past 10 years, and MALDI-MSI has been proven to provide an interesting and promising strategy for such investigations [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The washing method should be optimized for the target imaging molecules. Several washing protocols using organic solvents have been reported Andersson et al, 2008;Groseclose et al, 2007;Lemaire et al, 2006;Schwartz et al, 2003).…”
Section: Washingmentioning
confidence: 99%